PEMBENTUKAN RESILIENCE ANAK BERLATAR BELAKANG KONFLIK KELUARGA DALAM PERSPEKTIF SURAT YUSUF - Fatimah; Sri Wahyuni; Andi Sulasmi (Tarbawi: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to explore the story of the Prophet Yusuf (as), which suggests the formation of the ability to survive and recover from family conflict. This study uses a qualitative library research method. The primary data used are the Qur'an and tafsir books, while secondary data are obtained from books, scientific journals, and other relevant literature. Data collection techniques are carried out through the process of sorting, selecting, and summarizing data according to the discussion. Data analysis techniques are carried out by data reduction, data display, data verification, and drawing conclusions. This study found that the story of the Prophet Yusuf (as) contains fragmented stories that describe family conflict, starting from the story of the Prophet Yusuf's dream to his father, to the occurrence of various tragic events experienced by the Prophet Yusuf (as), such as being thrown into the bottom of a well, being found by travelers and sold into slavery, being accused of sexual harassment, as well as mental intimidation and threats of imprisonment. This study concludes that the Prophet Yusuf (as) was able to survive and overcome life's problems because of the resilience interventions given to him, in the form of; awakening self-strength (faith in Allah SWT, self-confidence, and optimism), providing support from others, teaching self-regulation, and strengthening self-efficacy. This research is limited by its descriptive analysis of limited data. Therefore, further studies with more extensive data coverage, particularly field data, are expected.